Toward a sociology of participation in adult education programs: The personal influence hypothesis - Wayne Babchuck; Sean Courtney (Adult Education Research Conference, 1994)
This study brings an interdisciplinary approach to the study of participation in adult education programs through the reconstruction of the sociological concept "personal influence." This approach holds important implications for issues surrounding recruitment, retention, and instruction of the adult learner.